LEARNING MOTIVATION MEDIATES THE INFLUENCE OF SELF-EFFICACY AND SPEAKING ANXIETY ON ENGLISH SPEAKING ABILITY - Rindika Pramadanti Rindi (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
Speaking English is a challenge that is considered difficult due to a lack of self-efficacy and motivation to learn, which causes anxiety. Therefore, this research tries to find out how self-efficacy influences students and reduces anxiety about speaking English so that it can increase students’ learning motivation in English-speaking skills. It is essential to see the strategies lecturers use to enhance self- efficacy, understand motivation, and reduce anxiety in speaking English. Several studies have examined learning motivation in improving English speaking skills, yet they did not specifically address factors, influences, and strategies related to self-efficacy and speaking anxiety. In this research, there were 136 respondents. They were university students in Jakarta, Indonesia. The data collection method used a questionnaire processed using SEM PLS version 3.2.9. This research found that several variables positively affected motivation to learn English, such as self-efficacy, speaking anxiety, and English-speaking skills. In addition, several variables can directly influence positive values ​​on English-speaking skills, such as self-efficacy and learning motivation, and negative values ​​on English-speaking skills, such as speaking anxiety. Apart from that, there is a direct positive influence on several variables that can influence speaking skills through controlling learning motivation, including self-efficacy and anxiety in speaking English.